P445 Prevalence rates of biosimilar discontinuation and switchback to originator biologics following non-medical switching: a meta-analysis of real-world studies. (25th January 2019) - Yifei, L; Skup, M; Yang, M; Qi, C; Doctor, T
Abstract: Background: To optimise clinical outcomes of biologics for autoimmune conditions, continued treatment of the same agent is critical, particularly for stable patients. The introduction of biosimilars to originator biologics has prompted non-medical switching (NMS) which may interrupt treatment consistency. This study examined prevalence rates of biosimilar discontinuation and switchback to originator following NMS. Methods: Real-world studies between January 2012 and August 2018 were identified through a systematic literature review. Discontinuation and switchback rates were extracted. A meta-analysis (MA) estimated the annualised discontinuation and switchback rates. A subsequent MA assessed annualised incremental discontinuation rate among studies that reported discontinuation for both cohorts: patients underwent NMS (switchers) and patients remained on originators (non-switchers). Results: A total of 62 studies were identified: 34 in gastroenterology, 31 in rheumatology, and 3 for both. Half reported switchback; only 9 reported discontinuation for both switchers and non-switchers. Mean/range sample size of NMS cohorts was 136/9–1641; mean/range follow-up was 10/3–24 months. Annualised discontinuation rate (95% Confidence Interval) was 21% (18%, 25%); switchback rate was 14% (10%, 17%) in all NMS patients and 62% (44%, 80%) in discontinuers. Mean sample size of switchers and non-switchers was 344/89–1621 and 768/19–2870, respectively; mean follow-up was 11/6–18 and 12/6–18 months. Annualised incremental discontinuation rate was 18% (4%, 31%), indicating a significantly higher rate in switchers. Conclusions: Biosimilar discontinuation is prevalent in the real world among patients who underwent NMS. Furthermore, switchback to originators is common following biosimilar discontinuation. Careful consideration is necessary when switching patients who are already on an originator to a biosimilar.